Design and Implementation of Single Phase Inverter Using FPGA - Muhammad Imran, Ahmad; Mohd Nazrin, Md Isa; Baharuddin, Ismail (Malaysian Invention and Design Society (MINDS), 2010)
Muhammad Imran Ahmad and his team from School of Computer & Communication Engineering won silver for Design and Implementation of Single Phase Inverter using FPGA. ITEX 2007, 18th - 20th May 2007 was held at Kuala Lumpur Convention Centre (KLCC), Kuala Lumpur.